2013
DOI: 10.1103/physreve.87.022129
|View full text |Cite
|
Sign up to set email alerts
|

Quantum collapse and the second law of thermodynamics

Abstract: A heat engine undergoes a cyclic operation while in equilibrium with the net result of conversion of heat into work. Quantum effects such as superposition of states can improve an engine's efficiency by breaking detailed balance, but this improvement comes at a cost due to excess entropy generated from collapse of superpositions on measurement. We quantify these competing facets for a quantum ratchet comprised of an ensemble of pairs of interacting two-level atoms. We suggest that the measurement postulate of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…From the inception of equilibrium thermodynamics in the 19th century to the present, a great multidisciplinary effort has been devoted to its extension to far-fromequilibrium situations, some of the most important cornerstones being the development of thermodynamics at the stochastic level [1,2] and its extension to the quantum regime [3][4][5]. Furthermore, motivated by the success of quantum information theory and the increasing control in preparation and manipulation of quantum states, the last decade has experienced a growing interest in understanding the thermodynamic implications of quantum features, such as quantum measurement [6][7][8][9], coherence [10][11][12][13], or quantum correlations [14][15][16][17][18][19]. In this context, inspired by the breakthrough work on the photo-Carnot engine driven by quantum fuel proposed by Scully et al [10], different theoretical studies recently focused on the implications for work extraction introduced by nonequilibrium quantum reservoirs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the inception of equilibrium thermodynamics in the 19th century to the present, a great multidisciplinary effort has been devoted to its extension to far-fromequilibrium situations, some of the most important cornerstones being the development of thermodynamics at the stochastic level [1,2] and its extension to the quantum regime [3][4][5]. Furthermore, motivated by the success of quantum information theory and the increasing control in preparation and manipulation of quantum states, the last decade has experienced a growing interest in understanding the thermodynamic implications of quantum features, such as quantum measurement [6][7][8][9], coherence [10][11][12][13], or quantum correlations [14][15][16][17][18][19]. In this context, inspired by the breakthrough work on the photo-Carnot engine driven by quantum fuel proposed by Scully et al [10], different theoretical studies recently focused on the implications for work extraction introduced by nonequilibrium quantum reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, motivated by the success of quantum information theory and the increasing control in preparation and manipulation of quantum states, the last decade has experienced a growing interest in understanding the thermodynamic implications of quantum features, such as quantum measurement [6][7][8][9], coherence [10][11][12][13], or quantum correlations [14][15][16][17][18][19]. In this context, inspired by the breakthrough work on the photoCarnot engine driven by quantum fuel proposed by Scully et al [10], different theoretical studies recently focused on the implications for work extraction introduced by nonequilibrium quantum reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, from the definitions of the average photon number and the entropy of the cavity field, we can infer that during the cavity evolution they are also closely related to the single excitation, double excitation processes, and the parameter ξ . Since the expressions of the average photon number and the entropy of the cavity field are very complicated we can only demonstrate how the parameter ξ and the reservoir's coherence a 23 and a 14 influence the dynamics of the cavity by numerical calculations. Only as an example, we plot Fig.…”
Section: Dynamics Of Cavity Field With a Nonequilibrium Reservoirmentioning
confidence: 99%
“…Recently, the thermodynamic effects of quantum coherence have attracted much attention and have been investigated based on quantum thermodynamics cycles. In this aspect, except for exploiting thermodynamics resource of quantum mechanical working materials [2][3][4][23][24][25][26][27][28][29][30] with the help of quantum engine and refrigerator models, the importance of reservoir manipulation has also been very recently acknowledged in the context of quantum thermodynamics: It has been recently demonstrated that superefficient operation of quantum heat engines may be achieved, e.g., by reservoir squeezing [31,32] and coherence [2][3][4] or using more general types of non-equilibrium reservoirs [33][34][35]. Especially, the exploration of reservoir's coherence in quantum thermodynamics has provoked great interest and the optical cavity model with a nonequilibrium coherent reservoir * Electronic address: zoujian@bit.edu.cn has been considered.…”
Section: Introductionmentioning
confidence: 99%
“…This principle, introduced as an effectively way to exorcize Maxwell's Demon, states that erasure of information is a logically irreversible process that must dissipate energy. More recently, developments in this directions include theoretical and experimental investigations of Landauer's principle and its consequences [4, 5], work extraction by feedback control of microscopic systems [6][7][8][9][10], and links between the second law of thermodynamics and two fundamental quantum mechanical principles, i.e., the wave-function collapse [11] and the uncertainty relation [12]. Here, we introduce a thermodynamic trade-off for information acquisition, which relates the uncertainty of the information acquired in a parameter estimation process with the dissipated work by the encoding process.…”
mentioning
confidence: 99%